2021
DOI: 10.1155/2021/5532672
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stochastic Optimization of Emergent Blood Collection and Distribution from Supply Chain Perspective

Abstract: In response to emergencies, it is critical to investigate how to deliver emergency supplies efficiently and securely to disaster-affected areas and people. There is no doubt that blood is deemed one of the vital relief supplies, and ensuring smooth blood delivery may substantially alleviate subsequent impacts caused by the disaster. Taking red blood cell products as the research object, this work proposes a four-echelon blood supply chain model. Specifically, it includes blood donors, blood donation houses, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The reason for the abundance of studies identifying MP is that author(s) desire to use a more general nomenclature for their proposed models, such as MP or mathematical model. In addition, a few studies among them introduce their mathematical model as a stochastic programming (Jabbarzadeh et al , 2014; Jin et al , 2021; Mohammadian-Behbahani et al , 2019) or robust optimization (Fereiduni and Shahanaghi, 2016; Haghjoo et al , 2020; Rahmani, 2019). Apart from these, few studies prefer mixed integer nonlinear programming (MINLP), integer nonlinear programming (INLP) and integer programming (IP) models, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the abundance of studies identifying MP is that author(s) desire to use a more general nomenclature for their proposed models, such as MP or mathematical model. In addition, a few studies among them introduce their mathematical model as a stochastic programming (Jabbarzadeh et al , 2014; Jin et al , 2021; Mohammadian-Behbahani et al , 2019) or robust optimization (Fereiduni and Shahanaghi, 2016; Haghjoo et al , 2020; Rahmani, 2019). Apart from these, few studies prefer mixed integer nonlinear programming (MINLP), integer nonlinear programming (INLP) and integer programming (IP) models, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that there are many studies devoted solely to the distribution of the platelets product. Besides, some studies follow the strategy of collecting blood products directly by apheresis (Ghatreh Samani et al , 2020; Ghatreh Samani and Hosseini-Motlagh, 2021a; Haeri et al , 2020; Hosseini-Motlagh et al , 2020a; Jemai and Sarkar, 2019; Jin et al , 2021; Larimi and Yaghoubi, 2019; Moslemi and Pasandideh, 2021; Osorio et al , 2018b). Apheresis is used to draw out only the needed components (platelets and red blood cells).…”
Section: Resultsmentioning
confidence: 99%